Single crystal X-ray structure of lawsone anion: evidence for coordination of alkali metal ions and formation of naphthosemiquinone radical in basic media - Salunke-Gawali, Sunita; Kathawate, Laxmi; Shinde, Yogesh; Puranik, Vedavati G.; Weyhermueller, Thomas (Journal of Molecular Structure, 2012)
2-hydroxy-1,4-naphthoquinone; Lawsone (Lw) is a natural compound found in henna leaves. The reaction of lawsone with `Na' metal (Lw-1), CH3COONa (Lw-2), NaOH (Lw-3), KOH (Lw-4), K2CO3 (Lw-5) and Tris(hydroxymethyl)aminomethane (Lw-6) were studied. Red orange solids obtained for Lw-1 to Lw-6 are characterized by Elemental Analysis, FTIR, (HNMR)-H-1 and EPR studies. The results reveal the coordination of alkali metals `Na' and `K' to lawsone anion. The single crystal X-ray structure of Lw-6 was solved and it crystallizes in triclinic space group P-1 with extensive hydrogen bonding network of C-H center dot center dot center dot O, N-H center dot center dot center dot O and O-H center dot center dot center dot O between cations and anions. Polycrystalline powder X-band EPR spectra of Lw-1 to Lw-5 shows signals similar to 2.004 at 133 K, while Lw-6 is EPR silent. The naphthosemiquinone (NSQ) radical formed in Lw-2 to Lw-5, is due to disproportion reaction of catechol and naphthoquinone. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: 2-Hydroxy-1; 4-naphthoquione; EPR; hydrogen bonding; Lawsone; Naphthosemiquinone radicals

Synthesis and molecular structure of a zinc complex of the vitamin K-3 analogue phthiocol - Kathawate, Laxmi; Sproules, Stephen; Pawar, Omkar; Markad, Ganesh; Haram, Santosh K.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2013)
The complex [Zn(phthiocol)(2)(H2O)(2)]; 1, where phthiocol is 2-hydroxy-3-methyl-1,4-naphthoquinone, has been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-vis spectroscopy, thermogravimetric (TG) analysis, electrochemical and single crystal X-ray diffraction studies. The v(C=O) stretch shifts to lower frequencies upon complexation of phthiocol to Zn2+. H-1 NMR spectra show an upfield shift of the benzenoid ring protons in 1. There is a bathochromic shift of the LMCT band in the UV-vis spectra of 1. Single crystal X-ray structure of 1 show distorted octahedral geometry around Zn2+. Two phthiocol ligands are in plane with the metal, while water molecules are trans to this plane. Coordination of deprotonated phthiocol ligands is `trans, trans' to Zn2+. Intra as well as intermolecular interactions are observed in 1. Molecules of 1 show three dimensional network through C-H center dot center dot center dot O and O-H center dot center dot center dot O interactions. Additional anodic peaks are observed in cyclic voltammogram of phthiocol ligand due to oxidation of reduced species formed during reduction. One-electron reduction of 1 is shown to be reversible and DFT studies define this redox event as ligand-centered. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonding; Naphthoquinone; Phthiocol; Trans coordination; Vitamin K-3; Zinc complex

Synthesis, characterization and molecular structures of homologated analogs of 2-bromo-3-(n-alkylamino)-1,4-napthoquinone - Salunke-Gawali, Sunita; Pawar, Omkar; Nikalje, Milind; Patil, Rishikesh; Weyhermueller, Thomas; Puranik, Vedavati G.; Konkimalla, V. Badireenath (Journal of Molecular Structure, 2014)
Four analogues of 2-bromo-3-(n-alkylamino)-1,4-napthoquinone (where n-alkyl is methyl in L-1Br, ethyl in L-2Br, propyl in L-3Br and butyl in L-4Br) are synthesized and characterized. A reaction mechanism is proposed for the formation of L-1 Br to L-4Br from the starting material 2,3-dibromo-1,4-naphthoquinone. The v(N-H) frequency in the FT-IR spectra is affected by the intramolecular hydrogen bonding in L-1Br to L-4Br and is observed similar to 3267 cm(-1) in L-2Br. A shift of similar to 25 cm(-1) is observed in the v(C-Br) frequency in all the compounds as compared to 2,3-dibromo-1,4-naphthoquinone (627 cm(-1)). A broad charge transfer band is observed between 400 and 600 nm in the UV-Vis spectra, which imparts red colour to all the compounds. Molecular structures of L-2Br and L-3Br were studied by single crystal X-ray diffraction studies. Molecules of L-2Br crystallize in Pca2(1), whereas the molecule L-3Br crystallizes in the P-1 space group. Molecules of L-2Br forms a polymeric chain through N-H...O interaction and forms beautiful butterfly like arrangement of molecules when viewed down the `a' axis. Ladder like polymeric chain of molecules is observed in L-3Br via C-H...O and N-H...O interactions. Every alternating neighbouring chains of L-3Br, show pi-pi stacking interactions between the quinonoid rings of the molecules, however this interaction is not observed in L-2Br. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: 2; 3-Dibromo-1; 4-naphthoquinone; Aminonaphthoquinone; hydrogen bonding; Michael addition; pi-pi stacking

First naphthosemiquinone complex of K+ with vitamin K3 analog: experiment and density functional theory - Kathawate, Laxmi; Gejji, Shridhar P.; Yeole, Sachin D.; Verma, Prakash L.; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2015)
Synthesis and characterization of potassium complex of 2-hydroxy-3-methyl-1,4-naphthoquinone (phthiocol), the vitamin K3 analog, has been carried out using FT-IR, UV-Vis, H-1 and C-13 NMR, EPR, cyclic voltammetry and single crystal X-ray diffraction experiments combined with the density functional theory. It has been observed that naphthosemiquinone binds to two K+ ions extending the polymeric chain through bridging oxygens O(2) and O(3). The crystal network possesses hydrogen bonding interactions from coordinated water molecules showing water channels along the c-axis. C-13 NMR spectra revealed that the complexation of phthiocol with potassium ion engenders deshielding of C(2) signals, which appear at delta = similar to 14.6 ppm whereas those of C(3) exhibit up-field signals near delta similar to 6.9 ppm. These inferences are supported by the M06-2x based density functional theory. Electrochemical experiments further suggest that reduction of naphthosemiquinone results in only a cathodic peak from catechol. A triplet state arising from interactions between neighboring phthiocol anion lead to a half field signal at g = 4.1 in the polycrystalline X-band EPR spectra at 133 K. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: C-13 NMR; DFT; hydrogen bonding; Naphthosemiquinone; Phthiocol; Vitamin K3

Naphthoquinone based chemosensor 2-(2 `-aminoethylpyridine)-3-chloro-1,4-naphthoquinone: detection of metal ions, X-ray -crystal structures and DFT studies - Patil, Amit; Ware, Anuja P.; Bhand, Sujit; Chakravarty, Debamitra K.; Gonnade, Rajesh G.; Pingale, Subhash S.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2016)
Naphthoquinone based Chemosensor 2; 2-(2'-aminoethylpyridine)-3-chloro-1,4-napthoquinone have been synthesized and characterized. Chemosensor 2 crystallizes in the orthorhombic space group Pbcn and shows extensive intramolecular as well as intermolecular hydrogen bonding interactions. Each molecule of Chemosensor 2 showed interaction with five neighboring molecules via C-H center dot center dot center dot N, N-H center dot center dot center dot N, C-H center dot center dot center dot Cl and C-H center dot center dot center dot O interactions. Slipped pi-pi stacking interaction was observed in adjacent quinonoid and benzenoid rings. Chemosensor abilities of Chemosensor 2 ligand have been evaluated with metal ions viz. Cu2+, Ni2+, Zn2+, Co2+, Fe3+, Mn2+, Cr3+, Hg2+, La3+ and Cd2+ in methanol, methanol-water mixture and in presence of mild base triethylamine. Stoichiometry of Chemosensor 2 with metal ions such as Cu2+, Ni2+, Zn2+ and Co2+ ions was determined by Jobs method in methanol and were found as 1:1 for Cu2+ and 2:1 for Ni2+, Zn2+ Co2+. The variation in the metal ligand ratio is observed in aqueous media for Cu2+. Chemosensor 2 can be used selectively for naked eye detection of Cu2+ ions. The association constant obtained in methanol shows the trend Cu2+>Ni2+>Co2+. Cu2+ and two (Ni-1 and Ni-2) Ni2+ complexes were synthesized. Ni-2 complex showed coordination of Chemosensor 2 ligands was through pyridine nitrogen's only. The Chemosensor 2 and its deprotonated forms in methanol, water and triethylamine were also studied by TD-DFT studies. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Chemosensor; hydrogen bonding; Naphthoquinone; pi-pi stacking; TD-DFT

Binding selectivity of vitamin K3 based chemosensors towards nickel(II) and copper(II) metal ions - Patil, Amit; Lande, Dipali N.; Nalkar, Archana; (Gejji, Shridhar P.; Chakrovorty, Debamitra; Gonnade, Rajesh; Moniz, Tania; Rangel, Maria; Pereira, Eulalia; Salunke-Gawali, Sunita (Journal of molecular Structure, 2017)
The vitamin K3 derivatives 2-methyl-3-[(pyridin-2-ylmethyl)-amino]-1,4-naphthoquinone (M-1), 2-methyl-3-[(pyridin-2-ylethyl)-amino]-1,4-naphthoquinone (M-2), 2-methyl-3-((2-(thiophen-2-yl) methyl)amino)naphthalene-1,4-dione (M-3) and 2-methyl-3-((2-(thiophen-2-yl)ethyl)amino)naphthalene-1,4-dione (M-4) have been synthesized, characterized and studied for their chemosensor abilities towards transition metal ions. Crystal structures of M-1 to M-4 revealed a variety of N-H center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions. Minor variations in such interactions by chemical stimuli such as metal ions, results in change in color that can be visualized by naked eyes. It has been shown that electronic structure and H-1 NMR, vibrational as well as electronic spectra from the density functional theory agree well with the experiments. The metal ion binding in ethanol, ethanol-water and in mild base triethylamine brings forth recognizing ability of M-1 toward Ni2+ whereas M-2 exhibits large sensing ability for Cu2+ ion. Interestingly M-1 display varying metal ion binding specificity in different solvents with the association constant in ethanol being 11,786 M-1 for Ni2+ compared to 9462 M-1 for the Cu2+. A reversal in preferential binding of M-2 with the respective association constants being 4190 M-1 and 6370 M-1 is discernible. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone Molecular-structures; Anthraquinone; Aqueous-solution; Chemosensor; Crystal-structures; Cu(II); Derivatives; DFT; Fluorometric Chemosensors; hydrogen bonding; Naphthoquinone; pi-pi stacking; Recognition; sensors